On the genesis of the Haumea system. Issue 2 (13th June 2016) - Campo Bagatin, A.; Benavidez, P. G.; Ortiz, J. L.; Gil-Hutton, R.
Abstract: The scenarios proposed in the literature for the genesis of the system formed by the dwarf planet 136108 Haumea, its two satellites and a group of some 10 bodies (the family) with semimajor axes, eccentricities and inclinations close to Haumea's values, are analysed against collisional, physical, dynamical and statistical arguments in order to assess their likelihood. All scenarios based on collisional events are reviewed under physical arguments and the corresponding formation probabilities in a collisional environment are evaluated according to the collisional evolution model alicandep . An alternative mechanism is proposed based on the potential possibility of (quasi-) independent origin of the family with respect to Haumea and its satellites. As a general conclusion the formation of the Haumea system is a low-probability event in the currently assumed frame for the evolution of the outer Solar system. However, it is possible that current knowledge is missing some key element in the whole story that may contribute to increase the odds for the formation of such a system.